IMPACT OF ADDING AJWAIN SEEDS TO THE MALE LAMBS’ RATIONS AS GROWTH PROMOTERS - S. El-Naggar,; S. Gad,; Z. Mahasneh,; M. Tawilla,; G Abou-Ward, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to investigate the impact of adding ajwain seeds to the rations of the growing Ossimi ram lambs on growth performance, nutrient digestibility, rumen liquor fermentation, and blood biochemical parameters. A total of 15 ram lambs, 5-6 months of age, were randomly allocated to the 3 treatments (5 lambs each). Lambs were fed a basal diet and regarded as a control group (T1), while the second (T2) and third (T3) treatments were fed on a basal diet plus 0.2 and 0.4 % of ajwain seeds respectively. At the end of the trial (150 days), three sheep from each treatment were used for a fourteen-day digestibility trial. Feed intake was similar for all groups. The treated groups exhibited higher (P